Creating customer value : the essentials of marketing - Learning Resources (Woodlands : Learning Resources.)
Tell stories,provide insight into the thinking of business and illustrate examples of real life case studies.
Guide-creating customer value-the essentials of marketing.
VHS.
Keywords: Consumer satisfaction; Customer services